Formation of mustard harvest structure elements depending on varietal characteristics - Mykolaiko, I. (Scientific Progress & Innovations, 2024)
Today, in Ukraine, the potential opportunities for increasing the productivity of crop production are only partially realized. One of the crops whose productive properties are not fully utilized is mustard. Most of the mechanisms of formation of increased productivity of plants of this culture are currently not fully understood and require additional research. In connection with this, we conducted many years of research in the conditions of the central part of the Forest Steppe of Ukraine. The purpose of which was to find out the peculiarities of the formation of the elements of the mustard crop structure depending on the varietal characteristics. It was established that the formation of the elements of the mustard crop structure depended on the biological characteristics of the varieties and the soil and climatic conditions of cultivation during all phases of plant growth and development. The most favorable conditions for the formation of biometric indicators and, accordingly, the yield of mustard seeds were in 2021. On average, over three years, the height of plants in the rosette phase, at the beginning of the growing season, in three varieties – Etalon, Tsarivna Pivnochi and Ariadna was almost the same (9.7 cm, 9.7 cm and 9.9 cm, respectively), while in the Oslava variety it was significantly higher and amounted to 10.4 cm. The lowest height indices were in the variety Pidpecheretska (9.0 cm). The height of plants varied by the phases of growth and development by varieties, and no single variety was found to be higher in all phases compared to other varieties. If in the rosette phase the height of plants of the Oslava variety was the highest (10.4 cm), then in the phases of butanization, flowering and ripening it was significantly higher in the Ariadna variety (38.9 cm, 66.6 cm and 103.4 cm, respectively). The number of pods per plant significantly varied depending on the varietal characteristics. The largest number of pods was formed on plants of varieties Ariadna – 68.7 pcs. and Oslava – 68.5 pcs. A much smaller number of pods was formed on plants of Etalon, Pidpecheretska and Tsarivna Pivnochi varieties. A similar dependence was observed for the number of stems. Most stems were formed by plants of Ariadna and Oslava varieties (3.8 pcs. and 4.0 pcs., respectively), while other varieties had significantly fewer stems. The analysis of variance established that the factor «growing conditions» had the greatest influence on the formation of the elements of the crop structure. The formation of the elements of the crop structure depended both on varietal characteristics and weather conditions during the years of the study. An increase in crop structure indicators contributed to the increase in seed productivity of mustard of all varieties, but seed quality – germination energy, germination and weight of 1000 seeds did not increase depending on the size of the elements of the crop structure, no significant difference was found in varieties.